Increasing prevalence of K65K and K66K in HIV-1 subtype B reverse transcriptase. (28th November 2016) - Telwatte, Sushama; Brumme, Chanson J.; Hearps, Anna C.; Latham, Catherine F.; Hayward, Joshua A.; Sonza, Secondo; Sluis-Cremer, Nicolas; Harrigan, P. Richard; Tachedjian, Gilda
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Synonymous substitutions K65K/K66K in HIV-1 reverse transcriptase alleviate fitness and fidelity defects in HIV-1 molecular clones harboring thymidine analogue mutations (TAMs); however, their potential for transmission and persistence is unknown. Here, we investigated the temporal appearance of K65K/K66K relative to TAMs in a HIV-1 cohort, their prevalence over time, and their impact on viral fitness in the context of patient-derived reverse transcriptase sequences. Methods: Retrospective analyses of the temporal appearance and longitudinal prevalence of synonymous substitutions and drug resistance mutations were performed using the British Columbia Centre for Excellence in HIV/AIDS Drug Treatment Program (DTP) database. Plasma-derived HIV-1 from the DTP was used to generate infectious molecular clones. Growth competition assays were performed to determine viral fitness. Results: The prevalence of K65K/K66K in drug-naïve individuals tripled from 11% in 1997 to 37% in 2014 ( P   <  0.0001, n  = 5221), with K66K mainly accounting for the increase. These mutations emerged in drug-treated individuals without TAMs in 14% of the cohort and conferred a fitness advantage in the context of patient-derived multidrug-resistant (MDR) virus in the absence of drug. Conclusion: The appearance of K65K/K66K in drug-treated individuals was largely independent of TAMs, suggesting alternative factors are likely associated with their emergence. The increasing K65K/K66K prevalence to over a third of treatment-naïve individuals in the mostly subtype B DTP cohort and their ability to confer a fitness advantage to multidrug-resistant virus might explain the transmission and persistence of virus harbouring K65K/K66K in untreated individuals, and highlights their role in adaptive HIV-1 evolution.